Menopausa, terapia de reposição hormonal e desempenho intelectual: um estudo transversal - Ana Leticia Camargos (2007)
Life expectancy of worlds population has been growing lately and age-related cognitive decline can be observed. Beyond age, there are others variables related to the cognitive decline. During life-span, women suffer the effects of menopause, and hormone replacement therapy (HRT) is indicated as a treatment of signals and physical symptoms. Despite decades of studies involving HRT, there is an ongoing controversy about the treatment and its effects on womens health. Recently, some studies indicated that HRT could modify age-related changes in cognitive decline. The aim of this essay was to investigate the effects of HRT on cognitive performance, as well as other variables related to the reproductive events and menopause. A cross-sectional and exploratory study was conducted with 125 women, age rage 65 and 94 years old. Two questionnaires were used to examine socioeconomic parameters, health conditions, menopause and HRT history. WAIS-III was administered as a measure of global and specific domains of cognitive abilities. Results show women that received hormone treatment reached superiors and statistically significant averages in FSIQ, PIQ, POI and in the subtests Picture Completion, Block Design, Arithmetic and Matrix Reasoning. So, women that received hormone therapy scored higher in tests involving fluid reasoning. Menarche, oral contraceptives use, numbers of pregnancy, range of reproductive age and menopause were associated to better performance. After age, education, socioeconomic status were adjusted, results became not significant. Multiple studies and the present one indicate that estrogen provides positive effects to cognition. However, these data are insufficient to indicate the use of HRT to prevent age-related cognitive decline. Further researches will be necessary to elucidate the benefits of HRT, hormone contributions and other factors related to menopause and HRT that might influence cognitive performance. Thus, new investigations about sexual hormones, menopause transition and its relation to cognition could contribute to improve quality of life in women at midlife and beyond.